"Incorrigible slag, " the case of Jennifer Murphy's HIV non-disclosure: Gender norm policing and the production of gender-class-race categories in Canadian news coverage. (May 2018) - Roth, Jenny; Sanders, Chris
Abstract: In Canada, HIV non-disclosure is a criminal offence captured under the rubric of aggravated sexual assault. How the crime is reported, however, supports dominant gender schema that are constituted in relation to class and race. This article uses the critical discourse paradigm to analyze the narrative discourses in news reports about Jennifer Murphy, charged with HIV non-disclosure, in relation to both gender policing and the broader case of her over-representation alongside the over-representation of racialized men. Doing a close reading of the narratives used by reporters, within their social, political, and ideological contexts reveals that, in the case of Murphy, as in the case of racialized men, unsafe sexual bodies are a trope for other power relations.